UV-light modulated Ti3C2Tx MXene/g-C3N4 heterojunction film for electromagnetic interference shielding. (July 2020) - Zhou, Qianfan; Qian, Kunpeng; Fang, Jianhui; Miao, Miao; Cao, Shaomei; Feng, Xin
Highlights: Ti3 C2 Tx /g-C3 N4 heterojunction films were assembled via a pressured-extrusion. The heterojunction films have high conductivity and good mechanical flexibility. The heterojunction films exhibit EMI SE of 42.99 dB with thickness of 28.2 µm. UV-light is assistance to modulate conductivity and EMI shielding performance. Abstract: With the mushrooming of smart electronic devices, ultrathin Ti3 C2 Tx MXene based EMI shielding materials with long term durability have aroused much interest. Herein, 2D Ti3 C2 Tx /g-C3 N4 heterojunction films were firstly assembled using cellulose nanofibrils (CNF) as green binder via a solution-based pressured-filtration process. The heterojunction film with Ti3 C2 Tx /g-C3 N4 mass ratio of 5:1 (28.20 µm in thick) exhibited distinguished performance with EMI shielding effectiveness of 42.99 dB in X-band and high tensile strength of 23.85 MPa. Specially, the generation of photo-electrons from g-C3 N4 nanosheets reduced TiO2 into lower valence states under 365 nm UV light-irritation, resulting in lower loss on electrical conductivity as well as EMI shielding performance compared to their unilluminated counterparts. The reduction on TiO2 offered by the g-C3 N4 enables the heterojunction film to be considered as a promising alternative EMI shielding material for future potential applications, because it can run long time just need UV light modulation.